Differential Expression of Drosophila Transgelins Throughout Development - Vakaloglou, Katerina M.; Mouratidou, Maria; Keramidioti, Athina; Zervas, Christos G. (Frontiers in Cell and Developmental Biology, 2021)
Transgelins are a conserved family of actin-binding proteins involved in cytoskeletal remodeling, cell contractility, and cell shape. In both mammals and Drosophila, three genes encode transgelin proteins. Transgelins exhibit a broad and overlapping expression pattern, which has obscured the precise identification of their role in development. Here, we report the first systematic developmental analysis of all Drosophila transgelin proteins, namely, Mp20, CG5023, and Chd64 in the living organism. Drosophila transgelins display overall higher sequence identity with mammalian TAGLN-3 and TAGLN-2 than with TAGLN. Detailed examination in different developmental stages revealed that Mp20 and CG5023 are predominantly expressed in mesodermal tissues with the onset of myogenesis and accumulate in the cytoplasm of all somatic muscles and heart in the late embryo. Notably, at postembryonic developmental stages, Mp20 and CG5023 are detected in the gut’s circumferential muscles with distinct subcellular localization: Z-lines for Mp20 and sarcomere and nucleus for CG5023. Only CG5023 is strongly detected in the adult fly in the abdominal, leg, and synchronous thoracic muscles. Chd64 protein is primarily expressed in endodermal and ectodermal tissues and has a dual subcellular localization in the cytoplasm and the nucleus. During the larval–pupae transition, Chd64 is expressed in the brain, eye, legs, halteres, and wings. In contrast, in the adult fly, Chd64 is expressed in epithelia, including the alimentary tract and genitalia. Based on the non-overlapping tissue expression, we predict that Mp20 and CG5023 mostly cooperate to modulate muscle function, whereas Chd64 has distinct roles in epithelial, neuronal, and endodermal tissues.